2020
DOI: 10.1080/14789450.2020.1766975
|View full text |Cite
|
Sign up to set email alerts
|

Network-based strategies in metabolomics data analysis and interpretation: from molecular networking to biological interpretation

Abstract: Introduction: Metabolomics has become a crucial part of systems biology; however, data analysis is still often undertaken in a reductionist way focusing on changes in individual metabolites. Whilst such approaches indeed provide relevant insights into the metabolic phenotype of an organism, the intricate nature of metabolic relationships may be better explored when considering the whole system. Areas covered: This review highlights multiple network strategies that can be applied for metabolomics data analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(64 citation statements)
references
References 127 publications
0
64
0
Order By: Relevance
“…The impact of method choice on biological interpretation of spectral data sets is further complicated by the selection of statistical analysis methods from a multitude of preprocessing algorithms and statistical pipelines. 21 23 In clinical environments, healthcare workers must, of necessity, prioritise patient safety over research sample collection and availability and handling of research samples are subject to the local clinical capabilities. Moreover, country-specific regulations can introduce deviations in sample collection and handling procedures.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of method choice on biological interpretation of spectral data sets is further complicated by the selection of statistical analysis methods from a multitude of preprocessing algorithms and statistical pipelines. 21 23 In clinical environments, healthcare workers must, of necessity, prioritise patient safety over research sample collection and availability and handling of research samples are subject to the local clinical capabilities. Moreover, country-specific regulations can introduce deviations in sample collection and handling procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in contrast to the conventional (also referred to as ‘classical’) molecular networking tool which relies solely on MS 2 information for molecular network generation, FBMN improves upon this by also incorporating MS 1 information such as retention time, ion mobility, and natural isotopic pattern. As a result, FBMN allows for spectral annotation, distinguishes isomers, as well as incorporates relative quantification information [ 15 , 16 ]. This method also offers the advantage of giving a more precise estimation of the relative ion intensity by making use of the LC-MS abundance of the features (i.e., peak area/height), as opposed to classical MN which makes use of the sum/total precursor count or spectral count [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Supporting the separation of the lipid composition of FF of the two groups, the corresponding chromatograms demonstrated differences in the relative abundance of features across several retention time frames and, in particular, in the typical retention time window of TAGs and cholesteryl esters ( Figure 1 C). Multiple studies have demonstrated that an evaluation of the correlations between variables can emphasize differences in the systemic response even when individual quantitative differences are minor [ 32 , 33 , 34 , 35 ]. We generated correlation matrices for significant correlations ( p < 0.001) between the 401 identified features.…”
Section: Resultsmentioning
confidence: 99%